Investigating the Determinants of Repeat Purchase Intentions for One Commune One Products in Digital Platforms - Giang, Nguyen Thi Phuong; Duy, Nguyen Binh Phuong; Hung, Le Huu; Huong, Le Thi Thuy; Phat, Nguyen Tan; Thao, Do Thanh; Tan, Thai Dong (International Review of Management and Marketing, 2025)
As technology continues to evolve, the rise of digital platforms has revolutionized the way consumers engage with products, especially in the context of e-commerce. This shift is particularly relevant for the promotion of OCOP (One Commune One Product) products, which are central to local economic development efforts in Vietnam. To succeed in this competitive landscape, it is essential to understand what drives consumers to repurchase OCOP products on digital platforms. This research focuses on evaluating key factors such as customer awareness, satisfaction, and the shopping experience that influence repeat purchases. The study draws on survey responses from 364 consumers who have previously bought OCOP products online, using Smart PLS 4.0 software to analyze the data. The findings highlight the importance of enhancing customer satisfaction and the overall digital experience to foster repurchase intentions, offering valuable insights for businesses looking to strengthen customer loyalty. The outcomes of this research also contribute to broader discussions on e-commerce and rural economic development in Vietnam.